Design of Vertically Stacked Waveguide Filters in LTCC - Shen, Tze-Min; Chen, Chi-Feng; Huang, Ting-Yi; Wu, Ruey-Beei (IEEE transactions on microwave theory and techniques, 2007)
This paper proposes four-pole quasi-elliptic function bandpass waveguide filters using multilayer low-temperature co-fired ceramic technology. The vertical metal walls of the waveguide resonators are realized by closely spaced metallic vias. Adjacent cavities are coupled by a narrow slot at the edge of the common broad wall or an inductive window on the sidewall. Two types of vertical coupling structures are utilized to achieve the cross coupling between nonadjacent resonators at different layers. With multilayer capability, there is more flexibility to arrange the cavities of coupled resonator filters in 3-D space. It is demonstrated by both the simulation and experiment that the proposed filter structures occupy a compact circuit area and have good selectivity. The filter with electric field cross coupling occupies a half area of a planar four-pole waveguide filter, while the filter with stacked vias cross coupling has 65% size reduction in comparison with a planar waveguide filter.